The spectrum of cutaneous polyarteritis nodosa. A case report of two contrasting cases and review of the literature. Issue 11 (27th November 2022) - Liang, Ian; Hamid, Mariya; Sebaratnam, Deshan; Manolios, Nicholas
Abstract: Cutaneous polyarteritis nodosa is a rare neutrophilic vasculitis. We present two cases that reflect the gamut of this disorder including one case whose delayed diagnosis led to permanent nerve deficit and scarring. Abstract : Cutaneous polyarteritis nodosa is a distinct entity different from polyarteritis nodosa that requires prompt recognition and treatment to prevent permanent neurological deficit and scarring.